Mental Rotation of Digitally-Rendered Haptic Objects - Tivadar, Ruxandra I.; Rouillard, Tom; Chappaz, Cédrick; Knebel, Jean-François; Turoman, Nora; Anaflous, Fatima; Roche, Jean; Matusz, Pawel J.; Murray, Micah M. (Frontiers in Integrative Neuroscience, 2019)
Sensory substitution is an effective means to rehabilitate many visual functions after visual impairment or blindness. Tactile information, for example, is particularly useful for functions such as reading, mental rotation, shape recognition, or exploration of space. Extant haptic technologies typically rely on real physical objects or pneumatically driven renderings and thus provide a limited library of stimuli to users. New developments in digital haptic technologies now make it possible to actively simulate an unprecedented range of tactile sensations. We provide a proof-of-concept for a new type of technology (hereafter haptic tablet) that renders haptic feedback by modulating the friction of a flat screen through ultrasonic vibrations of varying shapes to create the sensation of texture when the screen is actively explored. We reasoned that participants should be able to create mental representations of letters presented in normal and mirror-reversed haptic form without the use of any visual information and to manipulate such representations in a mental rotation task. Healthy sighted, blindfolded volunteers were trained to discriminate between two letters (either L and P, or F and G; counterbalanced across participants) on a haptic tablet. They then tactually explored all four letters in normal or mirror-reversed form at different rotations (0°, 90°, 180°, and 270°) and indicated letter form (i.e. normal or mirror-reversed) by pressing one of 2 mouse buttons. We observed the typical effect of rotation angle on object discrimination performance (i.e. greater deviation from 0° resulted in worse performance) for trained letters, consistent with mental rotation of these haptically-rendered objects. We likewise observed generally slower and less accurate performance with mirror-reversed compared to prototypically oriented stimuli. Our findings extend existing research in multisensory object recognition by indicating that a new technology simulating active haptic feedback can support the generation and spatial manipulation of mental representations of objects. Thus, such haptic tablets can offer a new avenue to mitigate visual impairments and train skills dependent on mental object-based representations and their spatial manipulation.